THE ROLE OF ATTITUDE AND FUTURE ORIENTATION IN STIMULATING SUSTAINABLE ENTREPRENEURIAL INTENTION - Filda Khoirun Nikmah; Ronald Haryanto; Sudarto Sudarto; Ekaningtyas Widiastuti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
During a period of fast economic expansion and worldwide environmental issues, an increasing number of business owners are incorporating sustainable practices in order to make sure their companies contribute positively to society and safeguard the environment. This research investigates how the consideration of future consequences, attitude, and perceived behavioral control impact the intention to become an entrepreneur among students at Universitas Jenderal Soedirman. A total of 77 participants completed a questionnaire to provide data for the study.   The results of the research suggest that the consideration of future consequences does not influence entrepreneurial intention.  However, Sustainable Entrepreneurial Intention is positively impacted by Attitude and Perceived Behavioral Control. This study provides implications for students to get support in increasing their confidence in running a sustainable business, campuses as educational institutions to develop business incubation programs that focus on sustainable entrepreneurship, and the government can design policies that support positive attitudes towards sustainable entrepreneurship among young people, such as incentives and training.